Corporate Cash Holdings and Advertising Spending After the Financial Crises - Supanvanij, Janikan (Journal of Applied Business and Economics, 2024)
This paper examines the link between a firm’s characteristics and advertising budget allocation. It also shows the firm’s behavior after the Asian financial crisis and the American subprime mortgage crisis. Results show that crises can significantly impact management decisions. They can influence how multinational companies plan for their future. The study also identifies the macroeconomic factors that can influence a firm’s decision to allocate funds.